STRUCTURAL PREDICTION OF HUMAN ZIP 2 AND ZIP4 BASED ON HOMOLOGY MODELLING AND MOLECULAR SIMULATION - SYAHPUTRA, GITA; GUSTINI, NUNIK; LOUISA, MELVA; PUTRA, MASTERIA YUNOVILSA; FADILAH, ADILAH (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to analyze the structural proteins of zinc transporters as the target for drug actions and their molecular interactions. Methods: The present study is about the homology modelling and analysis of the zinc transporter function using the in silico molecular modelling method. Homology modelling predicts the 3D structure of a protein based on the sequence alignment with one or more template proteins of known structure. This study using in silico molecular modelling method, explains the 3D structure of human ZIP 2 and ZIP4 with Ramachandran Plot analysis, physical and chemical characteristics, transmembrane prediction with structural biology, and binding site prediction through molecular docking simulation. Results: Based on the physicochemical properties of the 3D structure of the ZIP2 and ZIP4 proteins, each comprises 309 amino acids and 582 amino acids with pI values of 5.85 and 5.24. The amino acid composition analysis showed that both proteins contain many Leucine amino acids. The Ramachandran diagram concludes that both proteins are stable in the stereochemical conformation forming a secondary structure. The binding amino acids on ZIP2 include Glu281, His216, Ser284, and Arg46. The binding amino acids in ZIP4 include Gln148, Gln154, Thr155, His197, Ala138, and Lys157. Conclusion: Establishment of the structure and function of human ZIP2 and ZIP4 as zinc transporters in cell membranes and prediction of ZIP2 and ZIP4 binding sites through molecular dcoking.